2014
DOI: 10.3390/jmse2030534
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Annual Variability in Blue Whale Distribution off Southern Sri Lanka between 2011 and 2012

Abstract: Blue whale (Balaenoptera musculus) movements are often driven by the availability of their prey in space and time. While globally blue whale populations undertake long-range migrations between feeding and breeding grounds, those in the northern Indian Ocean remain in low latitude waters throughout the year with the implication that the productivity of these waters is sufficient to support their energy needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…The observation that blue whales (Balaenoptera musculus) feed off the southern coast of Sri Lanka during the NE monsoon period (de Vos et al, 2014) provided the motivation for this study. The NE winds, under Ekman dynamics, would generate a downwelling system (onshore Ekman flow) along the southern coast of Sri Lanka, resulting in a low primary productive system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that blue whales (Balaenoptera musculus) feed off the southern coast of Sri Lanka during the NE monsoon period (de Vos et al, 2014) provided the motivation for this study. The NE winds, under Ekman dynamics, would generate a downwelling system (onshore Ekman flow) along the southern coast of Sri Lanka, resulting in a low primary productive system.…”
Section: Discussionmentioning
confidence: 99%
“…During the SW monsoon, where the winds blow parallel to the coast, winds are upwelling favourable in terms of Ekman dynamics. Chlorophyll concentrations during the NE monsoon appear to be low, but there is evidence of high productivity through the documented feeding aggregations of blue whales (Balaenoptera musculus) along the southern coast of Sri Lanka (de Vos et al, 2014). Field observations have shown that ∼ 6-10 whales are sighted per day along the southern coast of Sri Lanka (data from 2009 to 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been established that there is a year-round resident population of Northern Indian Ocean blue whales B. m. indica in Sri Lanka (e.g. de Vos et al 2014) based only on observations of blue whales in the waters surrounding Sri Lanka during every month of the year (Ilangakoon & Sathasivam 2012). We similarly present evidence of blue whale sighting reports in New Zealand waters during every month of the year, which is corroborated by acoustic detections of the New Zealand blue whale call on 99.7% of recording days by at least 1 hydrophone during 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Line-transect surveys were conducted in both ecosystems using large research vessels (i.e. Black crosses represent Soviet whaling data (1963)(1964)(1965)(1966) collected during the November inter-monsoon and black circles represent Soviet whaling data (1963)(1964)(1965)(1966) and more recent sightings (1995, 1998, and 2012) collected within the monsoon seasons Mikhalev 2000;Ballance et al, 2001;de Vos et al, 2014b). Survey effort consisted of two observers using pedestal-mounted 25 9 150 binoculars to search for marine mammals during daylight hours; a third observer searched by eye or with 79 handheld binoculars and recorded both sightings data and survey conditions.…”
Section: Blue Whale Ecology and Datamentioning
confidence: 99%